Nongenomic effects of steroids on the nicotinic acetylcholine receptor - Barrantes, Francisco Jose (2000)
Nongenomic effects of steroids on the nicotinic acetylcholine receptor. A fast signaling mode of natural and synthetic steroids is exerted on some ion channels and cell-surface receptors. This activity contrasts with their classic mode of action, via intracellular receptors. Early studies from our laboratory demonstrated that spin-labeled androstanol and cholestane interact with the nicotinic acetylcholine receptor (AChR) and that lipid mobility at the lipid belt surrounding the AChR is reduced relative to that of the bulk membrane lipid. The occurrence of discrete and independent sites for phospholipids and sterols, both accessible to fatty acids, was subsequently disclosed in the native membrane. Synthetic and natural glucocorticoids were found to act as noncompetitive inhibitors of AChR function. The influence of different substituent groups in the cyclepentane perhydrophenanthrene ring on the channel-shortening potency of various steroids has also been assayed in muscle-type AChR, and we found a certain selectivity of this effect. Some organochlorine pesticides are xenoestrogens, that is, environmental agents capable of disrupting endocrine system signaling. We determined their effects on the AChR membrane using novel fluorescence techniques.